The Communication Process Analysis of The Yogyakarta Special Region Government in Distributing Social Security for The Elderly - Nur Izzaturrahmah; Dian Eka Rahmawati (Nakhoda: Jurnal Ilmu Pemerintahan)
Population aging is a global phenomenon that also occurs in Indonesia, including the Special Region of Yogyakarta (DIY) which has the highest number of elderly people in Indonesia in 2023, which is 16.69%. The elderly are a vulnerable group that requires special attention, especially in terms of social and economic welfare. The DIY Regional Government through the Social Security for the Elderly (JSLU) program aims to improve the welfare of poor or neglected elderly by providing basic needs-based assistance. This research analyses the DIY government's communication process in distributing JSLU. Using a qualitative approach, data was collected through secondary sources such as official government websites, credible online mass media, and scientific journals. This research focuses on the effectiveness of the communication process in distributing JSLU assistance which emphasizes the importance of effective and collaborative communication for the successful implementation of JSLU social policy. The results showed that the communication process in distributing JSLU social assistance was quite effective, especially in the communicator and communicant indicators, namely the DIY local government in collaboration with the DIY Social Service to convey messages to message recipients, namely the elderly. As well as in the indicator says what, namely the delivery of clear information through counseling. Information clarity and technology utilization also support community access. However, there are obstacles in the media or in which channel is used in the form of low accessibility of information for the elderly who are less familiar with technology and in the indicator with what effect, namely the lack of monitoring the socioeconomic impact of the program.